2020
DOI: 10.1002/pbc.28150
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of post‐induction resolution of pulmonary lesions in metastatic Ewing sarcoma

Abstract: Background Patients with metastatic Ewing sarcoma experience poor outcomes despite intensive systemic and local therapy. Early chemotherapy response of pulmonary metastases has been associated with prognosis in other pediatric malignancies. We reviewed the outcomes of patients with Ewing sarcoma and pulmonary metastases treated at our institution based on therapy received and early pulmonary response. Materials and methods We retrospectively reviewed patients with newly diagnosed Ewing sarcoma and pulmonary me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
(56 reference statements)
0
4
1
Order By: Relevance
“…While our study showed improved OS, studies by Raciborska et al., Spunt et al., and Halalsheh et al. found that patients with RCR had improved event‐free survival, but no improvement in OS in children with RCR 7,11,16 . Raciborska et al.…”
Section: Discussioncontrasting
confidence: 51%
See 4 more Smart Citations
“…While our study showed improved OS, studies by Raciborska et al., Spunt et al., and Halalsheh et al. found that patients with RCR had improved event‐free survival, but no improvement in OS in children with RCR 7,11,16 . Raciborska et al.…”
Section: Discussioncontrasting
confidence: 51%
“…Finally, Halalsheh et al. showed that patients with complete response of pulmonary nodules after induction chemotherapy had better 5‐year event‐free survival than those without complete response (45% vs. 6%; p < .01) 7 . Our study is larger than these studies, which could explain why we detected a difference in OS.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations